2017
DOI: 10.1038/s41598-017-11771-3
|View full text |Cite
|
Sign up to set email alerts
|

Oral fibroblasts modulate the macrophage response to bacterial challenge

Abstract: Tissue damage in chronic periodontal disease is driven by the host response to a dysbiotic microbiota, and not by bacteria directly. Among chronic inflammatory diseases of the oral cavity, inflammation and tissue damage around dental implants (peri-implantitis) is emerging as a major clinical challenge, since it is more severe and less responsive to treatment compared to inflammation around natural teeth. We tested whether oral fibroblasts from the periodontal ligament (PDLF), which are present around natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…However, the integrity of this soft tissue seal is also vulnerable to bacteria, especially immediately post‐surgery . A study by Zhao and colleagues and others presented the idea of a “race‐for‐the‐surface” between bacterial cells and mammalian gingival cells as a defining factor in the establishment of this soft tissue seal, and overall soft‐tissue health . Although this phenomenon has been primarily emphasized when considering soft‐tissue attachment implants, the race‐for‐the‐surface can occur on any component of the implant system that is simultaneously exposed to bacteria and cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the integrity of this soft tissue seal is also vulnerable to bacteria, especially immediately post‐surgery . A study by Zhao and colleagues and others presented the idea of a “race‐for‐the‐surface” between bacterial cells and mammalian gingival cells as a defining factor in the establishment of this soft tissue seal, and overall soft‐tissue health . Although this phenomenon has been primarily emphasized when considering soft‐tissue attachment implants, the race‐for‐the‐surface can occur on any component of the implant system that is simultaneously exposed to bacteria and cells .…”
Section: Introductionmentioning
confidence: 99%
“…33 A study by Zhao and colleagues and others presented the idea of a "race-for-the-surface" between bacterial cells and mammalian gingival cells as a defining factor in the establishment of this soft tissue seal, and overall soft-tissue health. 33,[37][38][39][40] Although this phenomenon has been primarily emphasized when considering soft-tissue attachment implants, the race-forthe-surface can occur on any component of the implant system that is simultaneously exposed to bacteria and cells. 39,41,42 Therefore, in order to understand the conditions in which this soft tissue health is compromised, components associated with early stage healing of gingiva need to be better investigated.…”
mentioning
confidence: 99%
“…The cDNA was treated with RNase H and purified using the QIAprep Spin Miniprep Kit (Qiagen). The primer sequences used were as follows: IL-1β forward, 5′-GCTGGAGGACTTT AAGGGTTAC-3′, and reverse, 5′-GATGTCTGGGTCTTGGTTCTC-3′; NLRP3 forward, 5′-AGCACCAGCCAGAGTCTAAC-3′, and reverse, 5′-CCCCAACCACAATCTCCGAAT-3′; ASC forward, 5′-AACCCAAGCAA GATGCGGAAG-3′, and reverse, 5′-TTAGGGCCTGGAGGAGCAAG-3′; Caspase-1 forward, 5′-CAAGGGTGCTGAACAAGG-3′, and reverse, 5′-GGGCATAGCTGGGTTGTC-3′; glyceraldehyde-3-phosphate dehydrogenase (GAPDH) forward, 5′-CATGTTCGTCATGGGTGTGA-3, and reverse, 5′-CAGGGGTGCTAAGCAGTTGG-3′ (Feria, Taborda, Hernandez, & Rugeles, 2018;Tzach-Nahman et al, 2017). Comparative quantification by PCR was performed with SYBR Premix Ex Taq using the Mx3000 P qPCR System (Agilent technologies, Santa Clara, CA).…”
Section: Quantitative Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%
“…It has been demonstrated that excessive inflammation in the gingival tissue, as well as an immune reaction triggered by the increased number of periodontal pathogens, such as Porphyromonas gingivalis (P.g. ), plays an important role in the severity and progression of periodontal diseases (3,4). Thus, the control of inflammation may help to delay disease progression or recover severe symptoms in periodontal diseases.…”
Section: Introductionmentioning
confidence: 99%